There Goes Gravity : How eBay Reduces Trade Costs - Lendle, Andreas; Schropp, Simon; Olarreaga, Marcelo; Vézina, Pierre-Louis (World Bank, Washington, DC, 2013)
This paper compares the impact of distance, a standard proxy for trade costs, on eBay and offline international trade flows. It considers the same set of 62 countries and the same basket of goods for both types of transactions, and finds the effect of distance to be on average 65 percent smaller on the eBay online platform than offline. Using interaction variables, this difference is explained by a reduction of information and trust frictions enabled through online technology. The analysis estimates the welfare gains from a reduction in offline frictions to the level prevailing online at 29 percent on average. Remote countries that are little known, with weak institutions, high levels of income inequality, inefficient ports, and little internet penetration benefit the most, as online markets help overcome government and offline market failures.